Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/cancers10090287
|View full text |Cite
|
Sign up to set email alerts
|

RKIP: A Key Regulator in Tumor Metastasis Initiation and Resistance to Apoptosis: Therapeutic Targeting and Impact

Abstract: RAF-kinase inhibitor protein (RKIP) is a well-established tumor suppressor that is frequently downregulated in a plethora of solid and hematological malignancies. RKIP exerts antimetastatic and pro-apoptotic properties in cancer cells, via modulation of signaling pathways and gene products involved in tumor survival and spread. Here we review the contribution of RKIP in the regulation of early metastatic steps such as epithelial–mesenchymal transition (EMT), migration, and invasion, as well as in tumor sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 237 publications
3
66
0
3
Order By: Relevance
“…This suggested that RKIP may not have a fundamental role in the primary tumour, but instead has great importance as a metastasis suppressor. In accordance, loss or reduction of RKIP expression is associated with malignancy and poor prognosis in several tumour types, as reported by our [16][17][18][19][20][21][22] and other groups [4,5,18,[23][24][25][26]. Biologically, RKIP is a multifunctional protein in carcinogenesis, regulating cellular growth [27,28], motility [29,30], epithelial-to-mesenchymal transition (EMT) [31] and invasion [32].…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…This suggested that RKIP may not have a fundamental role in the primary tumour, but instead has great importance as a metastasis suppressor. In accordance, loss or reduction of RKIP expression is associated with malignancy and poor prognosis in several tumour types, as reported by our [16][17][18][19][20][21][22] and other groups [4,5,18,[23][24][25][26]. Biologically, RKIP is a multifunctional protein in carcinogenesis, regulating cellular growth [27,28], motility [29,30], epithelial-to-mesenchymal transition (EMT) [31] and invasion [32].…”
Section: Introductionsupporting
confidence: 69%
“…This multifunctional capacity of RKIP is associated with its involvement in the modulation of several signalling pathways (Reviewed at [4][5][6][7][8]). This protein was first described as a regulator of the Raf-MEK-ERK pathway, acting as its endogenous inhibitor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with our histopathological results and previously published studies [14,36], we found that both RKIP mRNA and protein expression were significantly lower in melanoma cell lines than in primary cultures of melanocytes with the exception of the Mel-HO cell line; this cell line exhibited RKIP mRNA level similar to that observed on melanocytes but a reduced protein content that suggests the involvement of a post-transcriptional mechanism limiting translation. Of note, RKIP has been described as a target for several microRNAs able to regulate cellular protein level [2] RKIP is a multifunctional protein involved in carcinogenesis regulating cellular growth, motility, epithelial to mesenchymal transition and invasion [51][52][53]. Several authors have suggested that RKIP may not have a significant role in primary tumors but that instead, this protein could play an important role as a metastatic suppressor [5,[8][9][10][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Raf Kinase Inhibitor Protein (RKIP), also known as phosphatidylethanolamine-binding protein 1 (PEBP1), was originally described as an inhibitor of the MAPK and ERK1/2 pathway [1] although latter studies revealed its additional role as a regulator of other signaling cascades including the G-protein-coupled receptor (GPCR), glycogen synthase kinase 3β (GSK3β) and nuclear factor kappa B (NF-κB)-driven ones [2]. As a signaling switch, RKIP plays a role in essential processes such as differentiation, proliferation, and cell survival.…”
Section: Introductionmentioning
confidence: 99%